Status of aflatoxin contamination in cow milk produced in smallholder dairy farms in urban and peri-urban areas of Nairobi County: A case study of Kasarani sub county, Kenya - Kagera, Irene; Kahenya, Peter; Mutua, Florence K.; Anyango, Gladys; Kyallo, Florence; Grace, Delia; Lindahl, Johanna F. (Informa UK Limited, 2019)
Introduction: Milk consumption in Kenya supersedes other countries in East Africa. However, milk contamination with aflatoxin M1 (AFM1) is common, but the magnitude of this exposure and the health risks are poorly understood and need to be monitored routinely. This study aimed at assessing the awareness, knowledge and practices of urban and peri-urban farmers about aflatoxins and determining the levels of aflatoxin contamination in on-farm milk in a selected area within Nairobi County. Materials and methods: A cross-sectional study was undertaken to assess aflatoxin contamination levels of milk in Kasarani sub-county. A total of 84 milk samples were collected from small-holder dairy farms and analyzed for AFM1 using Enzyme-Linked Immunosorbent Assay (ELISA). Results and Discussion: Ninety nine percent of the samples (83/84) analysed were contaminated with AFM1. The mean aflatoxin level was 84 ng/kg with 64% of the samples exceeding the EU legal limit of 50 ng/kg. Whereas 80% of the farmers were aware of aflatoxin, there was no correlation between farmers’ knowledge and gender with AFM1 prevalence. Conclusion: This study concludes that AFM1 is a frequent contaminant in milk and there is need to enhance farmers awareness on mitigation.